Comparative efficacy different resistance training protocols on bone mineral density in postmenopausal women: A systematic review and network meta-analysis - Wang, Zhenyu; Zan, Xingchun; Li, Yongjie; Lu, Yue; Xia, Yuan; Pan, Xinyong (Frontiers in Physiology, 2023)
Objective: To systematically review the effects of different resistance training (RT) protocols on bone mineral density (BMD) in postmenopausal women. Methods: Randomized controlled trials (RCTs) on the resistance training in improving bone mineral density for postmenopausal women were searched in databases including ProQuest, PubMed, Cochrane Library, Embase, and Web of Science. The retrieval time range was from the establishment of the database to May 2022. The included literature was independently screened and relevant data was extracted by two reviewers. The systematic review followed the Joanna Briggs Institute (JBI) methodology for reviews of quantitative evidence. Quality of risk was assessed using the Physical Therapy Evidence Database (PEDro) scale, risk of bias was assessedusing the Cochrane RoB2 tool and a network Meta-analysis was performed on the data using Stata 16.0. Results: A total of 19 studies, which included 919 subjects, were eventually acquired. The results of the network Meta-analysis showed that moderate intensity resistance training was superior in improving lumbar spine bone mineral density (LS BMD) and femoral neck bone mineral density (FN BMD) compared to the control group (as per usual daily life), with a statistically significant difference (p < 0.05). There was, however, no statistically significant difference between the groups in terms of increasing total hip bone mineral density (TH BMD) and trochanter bone mineral density (Troch BMD), although moderate intensity training tends to increase bone mineral density (p > 0.05). In addition, when training frequency is taken into consideration, 3 days/week of moderate intensity training (3MI) was superior to 2 days/week (2MI) in improving lumbar spine bone mineral density , and moderate intensity training was superior to low and high intensity resistance trainings at training frequency of 3 day/week, with statistically significant differences (p < 0.05). The cumulative probability ranking results indicated that 3MI was the optimal option in improving lumbar spine, femoral neck, total hip and Troch bone mineral density. Subgroup analyses combining interventions time showed that for lumbar spine and femoral neck bone mineral density, 3MI protocol with intervention duration within 1 year (≤48 weeks) had a significant advantage over other interventions, while this advantage was no longer significant with the intervention duration of more than 1 year (>48 weeks). Conclusion: Current evidence shows that moderate intensity resistance training for 3 days/week can be preferred clinically to improve bone mineral density in postmenopausal women, and it is recommended that the duration of the same training should not exceed 1 year. Nevertheless, more high-quality studies are needed to verify the above conclusion.